Factors affecting continued usage intention of electronic government among public servants in Iraq - Munadil K. Faaeq (2014)
Electronic government (eG) system has become an important component of Information and Communication Technology provided by governments to facilitate all the transactions. This system has gained the popularity in developed and developing countries alike. Due to the inconsistency of the findings regarding the antecedents and consequences of usage behaviour of eG services, this study attempted to further explain this phenomenon in an unstable environment. Specifically, this study attempted to investigate the mediating role of Usage Behaviour on the relationships between the Unified Theory of Acceptance and Use Technology (UTAUT) antecedents and Continued Usage Intention. Additionally, this study attempted to investigate the moderating effect of Perceived Intensity of Civil Conflict (PICC) on the relationship between Usage Behaviour and Continued Usage Intention. In the relevant past literature, many theories have emphasized the necessity to establish the fit between various factors and Usage issues as the key success factor. However, this study integrated many theories such as the Expectation-Confirmation Theory, Conflict Theory, and UTAUT to examine the effect of various factors on Usage Behaviour and Continued Usage Intention of eG. To examine the hypothesized model, the data for this study were collected from the employees in the public universities. Out of 700 questionnaires distributed, 436 usable questionnaires were returned. This study employed the partial least squares structural equation modelling (PLS-SEM) to confirm the validity and reliability of the measurement model and to examine the structural relationships. The findings of the study confirmed the positive influence of Effort Expectancy, Performance Expectancy and Facilitating Conditions on the Usage Behaviour. In addition, the results supported the strong positive influence of usage behaviour on continued usage intention. While the moderating effect of PICC was not supported, usage behaviour was found to have a significant power to explain the effect of UTAUT variables on continued usage intention.